THE ROLE OF ISLAMIC KINGDOM CHARACTERS IN NUSANTARA IN MAINTAINING THE INDEPENDENCE OF THE REPUBLIC OF INDONESIA 1945-1950 - Agus mursidi; Dhalia Soetopo; Davi Grace Tiawan (International Jurnal of Education Schoolars, 2021)
The purpose of writing an article entitled "The Role of Islamic Kingdom Figures in the Archipelago in Maintaining the Independence of the Republic of Indonesia in 1945-1950" is to reveal what are the roles of Islamic royal figures and the roles and contributions of figures of the Islamic kingdom of the archipelago who helped play an important role so that lessons and the noble values of the leaders of the Islamic kingdom in their role in defending the independence of the Republic of Indonesia in 1945-1950. Qualitative research is research that intends to understand the phenomena experienced by research subjects such as behavior, perception, motivation, action etc. holistically and by means of descriptions in the form of words and language. While the type of research that the author does is historical research. The historical research method is a method that aims to make an objective and systematic reconstruction of the past through evidence to uphold facts and draw accurate conclusions. The results showed that the figures of the Islamic kingdom at that time also became an important part of the struggle to defend independence. With his various contributions through material and ideas as well as his ideas, he has become an important factor in Indonesia's success in defending independence. Without the involvement and role of the leaders of the Islamic kingdom at that time, it was impossible for the Indonesian nation at that time to succeed in seizing and defending its independence from the hands of the colonialists